Comparative Study of Acetylation Reactions to Mentol Compounds Using Lipase fromCandida Antarctica Recombined Aspergillus oryzae with Rhizomucor miehei - Hikmawati Widya Putri; Elvina Dhiaul Iftitah; Arie Srihadyastuti (Institut Atsiri Universitas Brawijaya, 2017)
Research about comparison an enzyme lipase of rhizomucormiehei and candida antarctica recombined aspergillusoryzae to catalyzes reaction asetilasi compound menthol by the difference of activity of the enzyme.Reaction done on condition temperature 50oc use up acetyl acetic anhidrid in a solvent n-heksan in a variety time.The results that is reaction asetilasi menthol use an enzyme lipase of candida antarctica recombined aspergillusoryzae and rhizomucormiehei by a unit activity different do not have a significant difference.The difference of the results the final product that is mentil acetate of these enzymes changed as from time to time produce the difference of the results at to 24 hours .The use of lipase of candida antarctica recombined aspergillusoryzae have a selectivity higher ( 96,93 % ) in forming mentil acetic than lipase of rhizomucormiehei with have the ability convert of 77,42 %.